Analisis Stabilitas Tanah Timbunan dengan Perkuatan Turap Kayu Galam di Daerah Rawa Kalimantan Selatan - Akhmad Gazali; Fathurrahman Fathurrahman (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
South Kalimantan is one of the areas that has a lot of swamps. The use of galam wood is an alternative to the construction of landslide resistors on the roadside in swamp areas. Landslides often occur on the edge of road piles in swamp areas. Not infrequently damage due to landslides on several roads. This study aims to determine the effect of galam wood plaster reinforcement on increasing soil carrying capacity and stability of embankment due to the operation of external forces. The factor of manual embankment slope safety with the fellenius slice method shows that SF = 0.857 <1.0